Forest management alternatives in juvenile Nothofagus pumilio (Lenga) in Land of fire Tierra del Fuego, Argentina - Ramos, Ricardo; Paredes, Dardo (Revista Mexicana de Ciencias Agrícolas, 2018)
In order to promote the integral use and development of silvicultural techniques to achieve sustainable management of lenga beech forests, the Forest Department of the Province Tierra de Fuego (Land of Fire), is implementing the project “Forest Management of juvenile Forest Reserves Production of Land of Fire”, articulated in the framework of the implementation of Resolution 256/09 concerning the Experimental Program Management and Conservation of Native Forests in Argentina. The General Directorate of Forests, through the creation of the Provincial Execute Unit of Forestry Programs (UEPPF for its acronym in Spanish), develops and applies silvicultural treatments on juvenile structures of lenga beech forests, generating experience, education and training of human resources in the work of thinning and spacing. Applications are being developed and trials of thinning and spacing at different intensities and criteria. 1) Crown thinning; 2) low thinning; 3) systematic spacing in strips of penetration; and 5) selective spacing. The application of the trials and techniques on juvenile structures, allow to generate knowledge and to establish differences in costs, operating efficiencies, and removable volumes depending on each situation. The information collected on this activity will be essential to perform monitoring of the remnant forest and be part of the guidelines that make the sustainable management of lenga beech forests in the province of Tierra de Fuego.
Keywords: costs; efficiency; silviculture; juvenile; forest